Toughening of Epoxy Resin via Silane Terminated Urethane Including Pre-Hydrolyzed Tetraethoxysilane - Kartal, Ilyas (Asian Journal of Chemistry, 2014)
In this study, firstly, silane terminated urethane was synthesized from poly(hexamethylene carbonate) diol and 3-isocyanatopropyl-trimethoxysilane. Prepared solutions of inorganic part (silane terminated urethane + pre-hydrolyzed tetraethoxysilane) were mixed with epoxy-hardener mixture to obtain hybrid solutions. Various hybrid solutions were prepared using different epoxy/inorganic part solution compositions. Furthermore, the effect of silane terminated urethane on the mechanical and morphological properties of epoxy was investigated. The structure and properties of the composites are characterized using a scanning electron microscopy. Epoxy/silane terminated urethane hybrid materials were subjected to examinations to obtain their tensile strength, three point bending properties, hardness, izod impact strength. Incorporation of silane terminated urethane into the epoxy resin greatly modified the impact behavior of hybrids.